2006
DOI: 10.1111/j.1468-3083.2006.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photochemotherapy in patients with cutaneous T‐cell lymphoma: is clinical response predictable?

Abstract: Seven out of 16 patients were classified as responders. Neither T-cell clonality nor any of the serum markers assessed pretreatment could reliably predict the response to ECP treatment. However, the individual relative changes in sIL-2R, neopterin and beta(2)-M during 6 months of ECP treatment coherently displayed correlation to the clinical response, as assessed after 12 months of ECP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Some studies suggested that LDH values could be regarded as an additional marker potentially associated with ECP response, 62,71 even if others did not completely confirm these findings. 67 On the other hand, what becomes evident from our data is that patients with a high tumor burden in the peripheral blood show a more aggressive clinical behavior and a significantly lower response to ECP; a possible suggestion in these patients could be therefore to establish a treatment able to induce a significant reduction in circulating leukemic cells and then initiate ECP.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Some studies suggested that LDH values could be regarded as an additional marker potentially associated with ECP response, 62,71 even if others did not completely confirm these findings. 67 On the other hand, what becomes evident from our data is that patients with a high tumor burden in the peripheral blood show a more aggressive clinical behavior and a significantly lower response to ECP; a possible suggestion in these patients could be therefore to establish a treatment able to induce a significant reduction in circulating leukemic cells and then initiate ECP.…”
Section: Resultsmentioning
confidence: 87%
“…Some studies suggested that LDH values could be regarded as an additional marker potentially associated with ECP response, even if others did not completely confirm these findings …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 This criterion does allow treatment of patients with a peripheral blood clone who may not have a high peripheral blood burden as this subset of patients may benefit from ECP. 46,47 The presence of a peripheral blood T-cell clone was included as a minor criterion as the presence of a peripheral blood T-cell clone does not correlate with response to ECP, 48,49 but these patients without a demonstrable clone would have to have other evidence of peripheral blood involvement such as a raised CD4 ⁄CD8 ratio > 10 or Sézary cell count > 10%. There is not enough literature on the treatment of erythrodermic CTCL without peripheral blood involvement to determine if this group of patients may benefit from ECP although some centres have noted a response in these patients.…”
Section: Patient Selection For Extracorporeal Photopheresis In Patienmentioning
confidence: 99%
“…Due to the findings of monoclonal T‐cells in peripheral blood of patients with CTCL, one explanation has been that ECP induces an anti‐clonotypic cytolytic immunity directly against tumour cells [17]. However, response has also been observed in CTCL patients lacking such a clone [38]. A major issue in CTCL, is whether ECP is inducing specific cytotoxicity to the lymphoma cells or alternatively is inducing specific or non‐specific regulatory T‐cells controlling the CTCL proliferation.…”
Section: Discussionmentioning
confidence: 99%